GENETIC DIVERSITY ANALYSIS IN HOUSE SPARROW (PASSER DOMESTICUS) USING MICROSATELLITE MARKERS IN PUNJAB, PAKISTAN - F. Batool; H. A. Khan; M. Saif-ur-Rehman (Journal of Animal and Plant Sciences, 2019)
The sparrow is a thriving ubiquitous species around the world, predominantly considered a serious bird pest in cultivations of variety of habitats.Genetic diversity one of key evolutionary variable and necessary for persistence and viability of such species. Present studies therefore, explored genetic variations in house sparrow using microsatellite markers. In all, 229 sparrows were captured with mist nets from Faisalabad and Rawalpindi while blood was taken from 193 samples and 16 microsatellite markers were incorporated to evaluate genetic relationships. Average allele numbers (Na) for all loci populations in Faisalabad were 4.10, and for Rawalpindi were 2.81, and corresponding heterozygosity (Ho) for the respective habitats were 0.51 and 0.38. Present studies, served apparent indicators for the genetic diversity analysis viz. allelic richness, heterozygosity, and also occurrence of intra and inter populationgenetic differentiation, and phylogenetic tree with atypical results for the sparrow populations.
Keywords: Genetic diversity; population structure; microsatellite markers; Passer domesticus.